Controle genético e expressão de genes associados à qualidade fisiológica de sementes de milho - Andrade, Thaís de (2015)
The demand for maize hybrid seeds with high quality is increasing in Brazil, mainly due to the adoption of advanced technologies by growers. It is known that physiological quality of maize seeds is influenced by genotype, becoming an important trait to be evaluated during the selection process in breeding programs. Several genes seem to be involved in the control of this trait, and those which encode the α-amylase enzymes are described as having the greatest influence on the physiological quality of maize seeds. However, recent researches has been observed that other genes may be associated with seed quality. Thus, the aim in this study was to evaluate the genetic control and the expression of genes associated with maize seed quality. For this purpose, a field was installed to obtain hybrid, reciprocal and inbred line seeds using partial dialel design. Five lines were used (30, 91, 57, 43, 64). The physiological quality of the seeds were accessed by water content, germination, first count of germination, germination speed index, cold test, accelerated aging and controlled deterioration. The heterosis effect, the general (GCA) and the specific (SCA) combining ability and the reciprocal effects were estimated. Proteomic analysis was performed for LEA proteins, α-amylase, MDH, ADH and PGI of seeds treated with ABA. Transcriptomic analysis was performed for the genes LEA, LEA D-34, α-amylase B73, α-amylase LOC 5425 and SOD. Heterosis and reciprocal effect was observed for physiological seed quality, furthermore, additive and dominant gene action were involved in genetic control of physiological quality of mayze seeds. ABA reduces the activity of α-amylase, germination and physiological seed quality of maize seeds. Expression of LEA proteins is related to physiological seed quality. There are heterosis and reciprocal effect in the expression of enzymes and proteins associated with physiological seed quality.